Identification and characterization of novel single nucleotide polymorphism markers for fat deposition in muscle tissue of pigs using amplified fragment length polymorphism - Pantaporn Supakankul (2018)
Copyright © 2017 by Asian-Australasian Journal of Animal Sciences. Objective: This study was conducted to identify and evaluate the effective single nucleotide polymorphism (SNP) markers for fat deposition in the longissimus dorsi muscles of pigs using the amplified fragment length polymorphism (AFLP) approach. Methods: Sixty-four selective primer combinations were used to identify the AFLP markers in the 20 highest- and 20 lowest-intramuscular fat (IMF) content phenotypes. Five AFLP fragments were converted into simple codominant SNP markers. These SNP markers were tested in terms of their association with IMF content and fatty acid (FA) composition traits in 620 commercially crossbred pigs. Results: The SSC7 g.4937240C > G marker showed an association with IMF content (p < 0.05). The SSC9 g.5496647-5496662insdel marker showed a significant association with IMF content and arachidonic levels (p < 0.05). The SSC10 g.71225134G > A marker revealed an association with palmitoleic and ω9 FA levels (p < 0.05), while the SSC17 g.61976696G > T marker showed a significant association with IMF content and FA levels of palmitoleic, eicosenoic, arachidonic, monounsaturated fatty acids, and ω9 FA levels. However, no significant association of SSC8 g.47338181G > A was observed with any IMF and FA levels in this study. Conclusion: Four SNP markers (SSC7 g.4937240C > G, SSC9 g.5496647-5496662insdel, SSC10 g.71225134G > A, and SSC17 g.61976696G > T) were found to be associated with IMF and/or FA content traits in commercially crossbred pigs. These findings provide evidence of the novel SNP markers as being potentially useful for selecting pigs with the desirable IMF content and FA composition.